Republic of Madagascar : Third Review Under the Extended Credit Facility and Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Republic of Madagascar. (IMF Staff Country Reports; Country Report, 2018)
The gradual economic recovery in this fragile state has persisted, with solid growth for the second consecutive year. Fiscal performance has been strong, inflation contained, and the external position robust. Implementation of the authorities' economic program, supported by an Extended Credit Facility (ECF) arrangement approved in July 2016, has been generally strong, buttressing the recovery.